2016
DOI: 10.1186/s12875-016-0483-2
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions to provide genetics education for primary care

Abstract: BackgroundAt least 10 % of patients seen in primary care are said to have a condition in which genetics has an influence. However, patients at risk of genetic disease may not be recognised, while those who seek advice may not be referred or managed appropriately. Primary care practitioners lack knowledge of genetics and genetic testing relevant for daily practice and feel inadequate to deliver genetic services. The aim of this systematic review was to evaluate genetics educational interventions in the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 28 publications
1
65
0
1
Order By: Relevance
“…24 Yet, these educational programs might not significantly change practice. 25 Patients and researchers face obstacles to the implementation of genomic medicine. Barriers to participation in genomic research studies include lack of community engagement, mistrust on the part of the patient, logistical barriers, and privacy and discrimination concerns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Yet, these educational programs might not significantly change practice. 25 Patients and researchers face obstacles to the implementation of genomic medicine. Barriers to participation in genomic research studies include lack of community engagement, mistrust on the part of the patient, logistical barriers, and privacy and discrimination concerns.…”
Section: Introductionmentioning
confidence: 99%
“…
on behalf of the CSER consortium, Sharon E. Plon, 25 and Gail P. Jarvik 1,31, * The Clinical Sequencing Evidence-Generating Research (CSER) consortium, now in its second funding cycle, is investigating the effectiveness of integrating genomic (exome or genome) sequencing into the clinical care of diverse and medically underserved individuals in a variety of healthcare settings and disease states. The consortium comprises a coordinating center, six funded extramural clinical projects, and an ongoing National Human Genome Research Institute (NHGRI) intramural project.
…”
mentioning
confidence: 99%
“…The majority of other educational projects to enhance understanding of genetics in primary care have been based in a single country, as was evidenced by the studies included in a systematic review (Paneque et al, 2016). For this and reasons of funding and travel and time commitment needed, access to genetics education by primary care practitioners was limited.…”
Section: The Interventionmentioning
confidence: 99%
“…As a foundation for the project, we undertook a systematic review of genetic education for primary care (Paneque et al, 2016). Using the results of that review and two workshops attended by partners of the project and key stakeholders (from primary care and public health), a genetics education curriculum for European professionals was prepared (www.…”
Section: The Interventionmentioning
confidence: 99%
“…Therefore, the expectation of patients carrying a BRCA1/2 mutation must be met by including GPs more efficiently in the BRCA1/2 care process and providing specific training to GPs. Previous studies have shown the effectiveness and ease of establishing training in oncogenetics (Houwink et al, 2014;Scheuner et al, 2014;Watson et al, 2001) or rare genetic diseases (Carroll et al, 2009;Paneque et al, 2016) for GPs.…”
mentioning
confidence: 99%